2007
DOI: 10.1038/nmat1962
|View full text |Cite
|
Sign up to set email alerts
|

High friction on a bubble mattress

Abstract: Reducing the friction of liquid flows on solid surfaces has become an important issue with the development of microfluidics systems, and more generally for the manipulation of fluids at small scales. To achieve high slippage of liquids at walls, the use of gas as a lubricant--such as microbubbles trapped in superhydrophobic surfaces--has been suggested. The effect of microbubbles on the effective boundary condition has been investigated in a number of theoretical studies, which basically show that on flat comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
265
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(300 citation statements)
references
References 19 publications
26
265
5
Order By: Relevance
“…Whereas the slip and viscous drag reduction have been extensively characterized in continuous flows by, for example, nanorheological measurements 22 and particle image velocimetry 23 , considerably less is known about the friction and dissipation in discrete droplets. This can be considered to originate from the contemporary characterization methods, such as the optical contact angle goniometry, that measure static or quasistatic properties of the interfaces and contact angles 24 .…”
mentioning
confidence: 99%
“…Whereas the slip and viscous drag reduction have been extensively characterized in continuous flows by, for example, nanorheological measurements 22 and particle image velocimetry 23 , considerably less is known about the friction and dissipation in discrete droplets. This can be considered to originate from the contemporary characterization methods, such as the optical contact angle goniometry, that measure static or quasistatic properties of the interfaces and contact angles 24 .…”
mentioning
confidence: 99%
“…However, the numerous experimental studies in the literature have reported (many erroneously, as discussed in Sects. 3.2.5 and 3.3.5) a wide range of slip lengths spanning from tens of nanometers to even millimeters on SHPo surfaces consisting of regular (periodic) structures (Ou et al 2004;Ou and Rothstein 2005;Choi et al 2006;Davies et al 2006;Truesdell et al 2006;Maynes et al 2007;Steinberger et al 2007;Byun et al 2008;Lee et al 2008;Tsai et al 2009;Jung and Bhushan 2010;Lee and Kim 2011a;Kashaninejad et al 2012;Kim and Hidrovo 2012;Maali et al 2012;Karatay et al 2013;Bolognesi et al 2014;Lee and Kim 2014) or random structures (Watanabe et al 1999(Watanabe et al , 2003Gogte et al 2005;Choi and Kim 2006a;Joseph et al 2006;Bhushan et al 2009;Govardhan et al 2009;Shirtcliffe et al 2009;Wang et al 2009;Kim and Hwang 2010;Li et al 2010;Wang and Bhushan 2010;Ming et al 2011;Srinivasan et al 2013). Sometimes orders-of-magnitude differences in the measured slip lengths were reported even on structurally similar SHPo surfaces (e.g., Lee et al 2008vs.…”
Section: The Motivation Of the Critical Reviewmentioning
confidence: 93%
“…Another indirect approach to slip measurement is to measure shear stress or frictional drag on a SHPo surface (Choi and Kim 2006a;Truesdell et al 2006;Steinberger et al 2007;Lee et al 2008;Bhushan et al 2009;Govardhan et al 2009;Wang et al 2009;Li et al 2010;Lee and Kim 2011a;Ming et al 2011;Maali et al 2012;Srinivasan et al 2013). Despite its relatively low accuracy (>1 µm in measurable slip length), the commercial rheometer has shown to be a convenient tool when measuring a (8) Q = − πr 4 8η dP dx 1 + 4δ r large slip length (e.g., >5 µm), as shown in Fig.…”
Section: Measurement Techniques Of Slip Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…The spanning gas-liquid interfaces, or menisci, that can protrude into or out of the fluid are then often close to being shear-free and allow slip. The drag reduction characteristics of such a surface have a strong dependence on the geometrical properties of these gas-liquid interfaces (Steinberger et al 2007) and it is an important matter to be able to quantify them. For shear flows with shear rateγ over such a surface occupying the plane y = 0 the velocity field far from the plane of the surface takes the form wherex is the flow direction.…”
Section: Introductionmentioning
confidence: 99%